PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 015 UJUNGBATU KABUPATEN ROKAN HULU - Susanti, Dewi; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the poor performance of fourth grade students learn IPA SDN 015 Ujungbatu Kabupaten Rokan Hulu, the acquisition value of the average student is 61.52 while the KKM specified is 68, other than that of the 23 students were only 11 or 47.83% students who achieve KKM. Troubleshooting learning, the researchers conducted the study by applying the learning model Contextual Teaching and Learning (CTL). This research is a classroom action research (PTK). This research was conducted in SDN 015 Ujungbatu Kabupaten Rokan Hulu, the research subjects fourth graders with the number of 23 students, which consisted of eight male students and 15 female students. This study was conducted by two cycles consisting of two meetings and a daily test at the end of the cycle, data collection techniques used were observation and written tests. The analysis technique used is descriptive analysis of activity data and the results of teachers and students learn science. The study states that the application of learning models CTL can improve learning outcomes IPA. This is evidenced by: (1) the activities of teachers in the first cycle of meetings I obtain a score of 10 (50.00%), meeting II was increased with a score of 12 (60.00%). In the second cycle was a meeting I obtained a score of 15 (75.00%) and at a meeting II obtained a score of 17 (85.00%); (2) the activity of students in the first cycle of meetings I gained a score of 9 (45.00%), at a meeting II was increased with a score of 11 (55.00%). In the second cycle meeting I obtained a score of 14 (70.00%) and in the second meeting of the second cycle obtain a score of 17 (85.00%); and (c) learning outcomes improved with the increasing number of students who reached the KKM of 11 students (47.83%) at the base score to 14 students (60.87%) in the first cycle and increased to 19 students (82.61% ) on the second cycle. This means that class into the sample has been completed in the classical style for the thoroughness of more than 80%, in addition to the average learning outcomes increased from a base score is 61.52 into 65.22 in the first cycle and 75.3 in the second cycle. Keywords: Learning Model CTL, IPA Learning Outcomes